2019
DOI: 10.1210/js.2019-00266
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor COUP-TFII Regulates Amhr2 Gene Transcription via a GC-Rich Promoter Element in Mouse Leydig Cells

Abstract: The nuclear receptor chicken ovalbumin upstream promoter–transcription factor type II (COUP-TFII)/NR2F2 is expressed in adult Leydig cells, and conditional deletion of the Coup-tfii/Nr2f2 gene impedes their differentiation. Steroid production is also reduced in COUP-TFII–depleted Leydig cells, supporting an additional role in steroidogenesis for this transcription factor. COUP-TFII action in Leydig cells remains to be fully characterized. In the present work, we report that COUP-TFII is an essential regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 75 publications
(100 reference statements)
4
37
0
Order By: Relevance
“…Both of them regulate Star [84] and Insl3 [85] gene expression in Leydig cells. Recently, it was shown that not only is NR5A1 capable of activating Amhr2 gene expression in Leydig cells, but also COUP-TF2, independently of NR5A1 activation [86]. No NR2F2 variants havebeen described in 46,XY individuals.…”
Section: Nr2f2: a "Pro-ovary And Anti-testis" Genementioning
confidence: 99%
See 1 more Smart Citation
“…Both of them regulate Star [84] and Insl3 [85] gene expression in Leydig cells. Recently, it was shown that not only is NR5A1 capable of activating Amhr2 gene expression in Leydig cells, but also COUP-TF2, independently of NR5A1 activation [86]. No NR2F2 variants havebeen described in 46,XY individuals.…”
Section: Nr2f2: a "Pro-ovary And Anti-testis" Genementioning
confidence: 99%
“…No NR2F2 variants havebeen described in 46,XY individuals. However, in mouse models, inactivation of Nr2f2 during prepubertal stages of male sexual development results in infertility, hypogonadism, and a block in spermatogenesis due to a failure of progenitor Leydig cells to mature and produce sufficient testosterone [86].…”
Section: Nr2f2: a "Pro-ovary And Anti-testis" Genementioning
confidence: 99%
“…AMH is mainly secreted by Sertoli cells, and its receptor AMHR2 is mainly present in progenitor LCs. 23 AMH has been shown to inhibit the proliferation of progenitor cells in the rat LC regeneration model, 24 and knocking out of Amh can actually induce LC hyperplasia. 25 AMH/AMHR2 usually transduces its signal through SMAD signal pathway and may inhibit the phosphorylation of AKT1 (effector of cell proliferation).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, in this study, we found that cypermethrin can up‐regulate the expression of Amh and its protein but not Dhh . AMH is mainly secreted by Sertoli cells, and its receptor AMHR2 is mainly present in progenitor LCs 23 . AMH has been shown to inhibit the proliferation of progenitor cells in the rat LC regeneration model, 24 and knocking out of Amh can actually induce LC hyperplasia 25 .…”
Section: Discussionmentioning
confidence: 99%
“…COUP-TFII can also regulate gene expression positively in complex with other DNA-binding TFs (e.g. SP1, HNF4 or PROX1) independently of cognate COUP-TFII DNA binding sites (Mehanovic et al, 2019) (Ktistaki and Talianidis, 1997) (Lee et al, 2009; Yamazaki et al, 2009)): These regulatory complexes are not associated with conserved genomic sites for COUP-TFII-DNA interaction, and thus appear to be driven by protein-protein recognition rather than by DNA codes. In contrast, while our gel shift assays show that DNA-bound COUP-TFII can recruit NKX2-3 in the absence of a canonical NKX motif, this interaction is not sufficient to drive reporter expression in our systems: Activating NKX-COUP-TFII heterodimers may require stabilization by canonical NCCE in which both TFs bind their cognate motifs.…”
Section: Discussionmentioning
confidence: 99%